HUBUNGAN POLA KONSUMSI TERHADAP PENYAKIT DIABETES MELITUS DI DESA ALUR CEMPEDAK - Azmi, Nurul; Siregar, Putra Apriadi; Saphira, Sindi Julfa; Sipahutar, Nurida; Sitorus, Ardiansyah Pratama; Handayani, Fitri (Journal of Gender and Social Inclusion in Muslim Societies, 2024)
Diabetes mellitus (DM) is a serious medical condition. Based on international research data, the prevalence of diabetes mellitus reached 8.8% during 2015 and affects 415 million people worldwide. By 2040, this figure is projected to increase to 642 million. Diabetes mellitus is the sixth leading cause of death in the world. In Indonesia, the prevalence of DM is around 4.8%. The goal of this research is to examine the association factors connected with diet, gender, and status involved in exercising while suffering from diabetes mellitus. Methodology used This research uses a quantitative approach along with a cross sectional analysis method, The sample in this study, specifically the people in Alur Cempedak Village, Pangkalan Susu District, Langkat Regency which amounted to 357 respondents, Data collection through interview research tools with research instruments using questionnaires. The variables studied were age, gender, and employment status. The results obtained Table 1 displays the risk variables for diabetes according to different attributes. Significant predictors (p<0.05) included gender, age, occupation, exercise, and the amount of sweet, salty, and fatty foods consumed. Men were 1.163 times more likely to develop diabetes than women, people over 50 years old were 0.54 times more likely to develop diabetes, and consuming sugary foods increased the risk of diabetes by 1.01 times. Eating high-fat foods had a risk of 0.893 and high-salt foods 1.404. This finding is different from Arithka Ayu's research in 2019 which showed the danger of eating salty foods by 1.404 compared to sweet and fatty foods.